2004
DOI: 10.1159/000080228
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Activation Shortly after Cochlear Implantation

Abstract: We evaluated the cortical activations in postlingually deaf cochlear implant (CI) users in the early period (0–2 months) of CI usage. The subjects were 8 early CI users and 8 normal subjects. With tone burst stimuli (1 kHz) delivered to the right side, strong and broad activation of the ipsilateral (right) primary auditory cortex with 2 peaks and weaker activation of the contralateral (left) temporal lobe were observed in early CI users, in a clear contrast with the normal subjects in whom activation was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 74 publications
(57 reference statements)
2
11
0
Order By: Relevance
“…Based on current findings in the hearing auditory system (Sakai & Suga, 2002) we assume that the cortical reorganization is the source of subcortical reorganizations and not vice versa (for discussion, compare Kral & Tillein, 2006). Cortical reorganization after cochlear implantation in humans has been shown to extensively include higher-order areas Ito et al, 2004;Lee et al, 2001;Naito et al, 1997).…”
Section: Cross-modal Plasticity In the 'Deaf' Auditory Cortexmentioning
confidence: 99%
“…Based on current findings in the hearing auditory system (Sakai & Suga, 2002) we assume that the cortical reorganization is the source of subcortical reorganizations and not vice versa (for discussion, compare Kral & Tillein, 2006). Cortical reorganization after cochlear implantation in humans has been shown to extensively include higher-order areas Ito et al, 2004;Lee et al, 2001;Naito et al, 1997).…”
Section: Cross-modal Plasticity In the 'Deaf' Auditory Cortexmentioning
confidence: 99%
“…Reduced input to the brain from impaired auditory pathways results in significant changes in the central auditory system [12] and is accompanied by a recruitment of deprived cortices in response to input from the intact senses [1317]. When auditory input to the brain is reintroduced, this novel auditory experience may itself induce additional plasticity [18]. The sensory reafferentation provided by the CI thus offers a unique opportunity to study the effects of preceding deafness on functional brain organization.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, monaural acoustic stimulation under fMRI or PET had revealed a stronger lateralization of the cortical response towards the contralateral hemisphere and a more restricted activation in normal-hearing subjects compared with monaurally or binaurally deaf subjects, who were stimulated either acoustically or via CI Ito et al, 2004;Scheffler et al, 1998]. Therefore, laterality indices (LI) were calculated for all participants with 'perfect' or 'acceptable' activation as LI = (V contr -V ipsi )/(V contr + V ipsi ), where V contr and V ipsi denote the number of the activated voxels in the contralateral and ipsilateral cortices, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…With normal-hearing subjects, however, unilateral acoustic stimulation evoked strong contralateralization of cortical fMRI response, and a binaural stimulation evoked a nearly balanced activation [Ito et al, 2004;Scheffler et al, 1998]. described a shift from contralateral activation during normal bilateral hearing to bilateral activation after a sudden unilateral hearing loss due to cochlear nerve resection.…”
Section: Lateralitymentioning
confidence: 99%